Creative Industry Development Model as an Economic Support in Surabaya - Martha Hendrati, Ignatia; Khoiro Taufiqo, Fifi Ulid (Opción, 2019)
This paper creative industry for supporting the development of the City of Surabaya, Indonesia. Creative industries come from individual abilities re- garding skills and creativity with creative exploration, thus opening up em- ployment and welfare opportunities. aimed at elaborating the existence and exploring the ways how to take advantage of. The paper concludes that the city of Surabaya has considerable opportunities in developing creative indus- tries, but also has challenges in its development. In addition, there is a need for the need for a creative industry coordination institution and strong commit- ment and consistency in collaboration and further implementation.